The Application of Role-Playing Learning Methods in Javanese Language Learning Upload Material Grade 9 SMP N 2 Gemuh - Indriana, Melinda Sischa; Werdiningsih, Yuli Kurniati; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
This study aims to describe the results of the application of role-playing learning methods in Javanese language learning upload materials in grade 9 of SMP N 2 Gemuh in the 2023/2024 school year. This research was motivated by the low ability of grade 9 students in uploading and the use of inappropriate learning methods so that learning became boring and students seemed less active. Related to this problem, the formulation of the problem in this study is how to apply and the results of the application of role-playing learning methods in the upload material for grade 9 Javanese language learning at SMP N 2 Gemuh. The design in this study was a one-shoot case study using only one class without a control group or comparison. The data analysis technique used in this research is quantitative descriptive. The data in this study was obtained by observation and through interviews conducted with a Javanese maple teacher in one of the students. While the data collection techniques in this study used test and non-test techniques. Thus, the results of the application of role-playing methods in the upload material for grade 9 Javanese language learning at SMP N 2 Gemuh can have an influence on learning achievement.